The strategic approach of America and India to the Indo-Pacific region - Mehdi Amiri; mehrshad ghafarizade (رهیافتهای سیاسی و بین المللی)
Indo-Pacific is the most dynamic and diverse region in the world. The region has become the major hub of world politics and economy. During the last decade, global attention to the region has increased strategically and economically. The rise of China as a great power and its incising influence has been a challenge for the hegemony of the United States at the level of the international system and India at the regional level. The United States is India's most comprehensive strategic partner. Both countries have complementary strategic interests; America wants to maintain its economic and military hegemony in the world, and India, in turn, seeks to expand security relations with the United States in order to facilitate the country's transformation into a regional power in the future. The main question of the article is, what is the United States and India’s approach towards the Indo-Pacific region? The hypothesis of the article is that India has a "leading" or major role in the United States’ Indo-Pacific strategy, but this does not mean a military and security alliance between the two countries, because India is trying to maintain its strategic autonomy in regional issues. The two countries have different approaches in the geographical definition of the region, the type of confrontation with the rise of China and the centrality of ASEAN in the region. This research has been prepared with an analytical approach and using the security strategies of the two countries.